A Web-Based Personnel Information System with Geolocation Using User-Centered Design: A Usability Evaluation with SUS - Muhammad Rizki Fadillah; Aninda Muliani Harahap (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Digital transformation in public administration requires integrated and efficient personnel information systems. However, personnel management at the Ministry of Religious Affairs Office of Simalungun Regency remains semi-manual and fragmented, resulting in process inefficiencies, data inconsistencies, and limited information accessibility. This study seeks to develop and assess a web-based personnel information system by applying the User-Centered Design (UCD) approach to enhance service quality and optimize the user experience. The UCD method was applied iteratively through context analysis, user requirement specification, solution design, and usability evaluation. The developed system integrates geofencing-based attendance with real-time location monitoring, workflow-based leave management, and Key Performance Indicator (KPI)-based performance evaluation within a centralized platform. The usability assessment using the System Usability Scale (SUS) with 30 respondents yielded a mean score of 91.25 (Grade A), indicating excellent usability and high user acceptance. The findings further demonstrate that the integration of User-Centered Design (UCD) principles and geofencing technology contributes to improved attendance accuracy, administrative efficiency, information accessibility, and transparency in personnel management. The proposed system contributes to digital government transformation by providing an integrated and user-oriented solution for personnel administration in public sector organizations.